2009
DOI: 10.3113/fai.2009.0680
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Paratenon Release for Non-Insertional Achilles Tendinopathy

Abstract: A minimally invasive circumferential paratenon release and peritendinous steroid infusion was a simple method to treat non-insertional Achilles tendinopathy and had low morbidity in our series. This technique has become our preferred primary surgical intervention for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
0
22
0
1
Order By: Relevance
“…16 (19)B. Minimally invasive: US–CD-guided release ventral AT by use of a needle Alfredson [1] a 72 (88)Minimally invasive: US–CD-guided release ventral AT3014 Alfredson et al [3]13 (13)Minimally invasive: US–CD-guided release ventral AT4617 Calder et al [6]32 (34)Minimally invasive: Release AT and excision plantaris tendon5921 Maffulli et al [20]39 (39)Minimally invasive: multiple percutaneous longitudinal tenotomies5920 Naidu et al [24]26 (29)Minimally invasive: circumferential AT release with a tracheal hook + peritendinous infusion of corticosteroids4017 Testa et al [36]63 (63)Minimally invasive: multiple US-guided percutaneous longitudinal tenotomies6520Endoscopic procedures Maquirriain [22]24 (27)Endoscopic: debridement paratenon + two longitudinal tenotomies5213 Pearce et al [30]11 (11)Endoscopic: debridement paratenon + release of plantaris tendon6013 Steenstra and van Dijk [33]16 (16)Endoscopic: debridement paratenon + release of plantaris tendon2611Open surgery: gastrocnemius lengthening Duthon et al [10]13 (15)Open surgery: gastrocnemius lengthening6515Open surgery: autologous tendon transfer Martin et al [23]44 (4...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…16 (19)B. Minimally invasive: US–CD-guided release ventral AT by use of a needle Alfredson [1] a 72 (88)Minimally invasive: US–CD-guided release ventral AT3014 Alfredson et al [3]13 (13)Minimally invasive: US–CD-guided release ventral AT4617 Calder et al [6]32 (34)Minimally invasive: Release AT and excision plantaris tendon5921 Maffulli et al [20]39 (39)Minimally invasive: multiple percutaneous longitudinal tenotomies5920 Naidu et al [24]26 (29)Minimally invasive: circumferential AT release with a tracheal hook + peritendinous infusion of corticosteroids4017 Testa et al [36]63 (63)Minimally invasive: multiple US-guided percutaneous longitudinal tenotomies6520Endoscopic procedures Maquirriain [22]24 (27)Endoscopic: debridement paratenon + two longitudinal tenotomies5213 Pearce et al [30]11 (11)Endoscopic: debridement paratenon + release of plantaris tendon6013 Steenstra and van Dijk [33]16 (16)Endoscopic: debridement paratenon + release of plantaris tendon2611Open surgery: gastrocnemius lengthening Duthon et al [10]13 (15)Open surgery: gastrocnemius lengthening6515Open surgery: autologous tendon transfer Martin et al [23]44 (4...…”
Section: Resultsmentioning
confidence: 99%
“…15/19 (78.9 %)B. 4/19 (21.1 %) Alfredson [1] a,b 81/88 (92.0 %)7/88 (8.0 %) Alfredson et al [3]11/13 (84.6 %)2/13 (15.4 %) Calder et al [6] c 22/32 (69 %)10/32 (31 %) Maffulli et al [20]30/39 (76.9 %)9/39 (23.1 %) Naidu et al [24] c 24/26 (92 %)2/26 (7.7 %) Testa et al [36]47/63 (74.6 %)16/63 (25.4 %)Endoscopic procedures Maquirriain [22] c 24/24 (100 %) Pearce et al [30]8/11 (73 %)3/11 (27 %) Steenstra and van Dijk [33]Open surgery: gastrocnemius lengthening Duthon et al [10] c 12/13 (92.3 %)1/13 (7.7 %)Open surgery: autologous tendon transfer Martin et al [23]37/44 (86 %)6/44 (13.8 %) a Same study comparing release of ventral AT with knife versus needle b Study includes patients who received bilateral surgical treatment; outcome reported on individual tendons c Study included patients who received bilateral surgical treatment; outcome reported on patient level …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Naidu et al [30] reported a complication rate of 7 %, mainly due to delayed wound healing.…”
Section: Discussionmentioning
confidence: 98%